2021
DOI: 10.3390/jcm10215104
|View full text |Cite
|
Sign up to set email alerts
|

Treatment Options for Elderly/Unfit Patients with Chronic Lymphocytic Leukemia in the Era of Targeted Drugs: A Comprehensive Review

Abstract: Chronic lymphocytic leukemia (CLL) incidence increases with age reaching 37.9/100,000 in patients over 85 years. Although there is no standardized geriatric tool specifically validated for CLL, a correct framing of the fitness status is of critical importance to individualize treatment strategies. Based on the evidence available to date, frontline chemoimmunotherapy has an increasingly narrowing application, being eligible for candidacy only in elderly fit patients without or with minimal geriatric syndromes. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 63 publications
1
2
0
Order By: Relevance
“… 13-15 Studies in which ECOG PS showed a negative impact included more unfit and, on average, older patients, whereas a higher CIRS showed an impact in younger and fit patients, independently of the treatment received. 16 Our results align with this observation, considering that our cohort includes exclusively unfit patients, almost all of whom are older than 65 years.…”
supporting
confidence: 88%
“… 13-15 Studies in which ECOG PS showed a negative impact included more unfit and, on average, older patients, whereas a higher CIRS showed an impact in younger and fit patients, independently of the treatment received. 16 Our results align with this observation, considering that our cohort includes exclusively unfit patients, almost all of whom are older than 65 years.…”
supporting
confidence: 88%
“…In clinical trials, when considering patients with comorbidities, fitness is assessed based on CIRS and creatinine clearance, calculated by Cockcroft-Gault [59,60]. CIRS allocates a severity level specific to each system from 0 to 4, depending on the impairment, while creatinine clearance provides a precise assessment of renal impairment [61,62]. CIRS assesses comorbidities in different organ systems by rating 13 body systems on a fivepoint pathophysiology severity scale [63].…”
Section: Criteria Of Assessment Of Treatment Fitness (Tablementioning
confidence: 99%
“…In the preceding era, age was firmly established as an unfavorable predictor [20][21][22][23]. However, the influence of age on prognosis with targeted therapies seems to be less pronounced, at least in clinical trials [24][25][26][27][28].…”
Section: Age and Cllmentioning
confidence: 99%